Community Empowerment Through the Sustainable Food House Program Using Hydroponic Planting Media in the Sungai Batu Dendeng Community Care Group - Dwi Septia Kari; Kormil Saputra; Syamsuddin, Syamsuddin (Future Tecno-Science Publisher, 2025)
The purpose of this Community Service Program (KKN) is to try to introduce the community to the hydroponic planting system. Hydroponic planting media itself is a method of farming using water as the main focus. Hydroponics is a method that can be developed and applied in the household sector. The goal to be achieved from this KKN activity is to develop hydroponic land that can be utilized by residents, reduce household waste such as plastic bottles that can be utilized as hydroponic planting media, and invite the community to participate in protecting their environment and develop the KMPS Batu Dendeng river community where the river is the main focus of the KMPS community, Dasan Geres Selatan Village. The results of the development of this method are expected to make the community better understand the hydroponic farming system and be able to develop it independently and utilize used waste and household waste, such as plastic bottles. So that it can reduce the problem of environmental pollution in the area. One simple way that can be used to increase public awareness of the environment is to utilize used plastic bottles as a planting medium using the concept of wick hydroponics or wick system.